INTENSIFICATORS AS PRAGMATIC POTENTIAL MARKERS OF SPANISH AUTHOR ARTICLES - Artemova , Lyudmila (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
This article treats the investigation of language means of pragmatic component intensification of Spanish author column. We define these means as intensificators, which are used to carry out the author’s pragmatic aim, which is to underline the influence on the addressant, activating the expressive (evaluating and emotive) dominant of expression. Those can be lexical units that form ascendent and descendent gradations. Also, they can be “inner intensificators”, to be exact marked with expressiveness as for their semantic meaning lexical items. The particular attention is paid as well to the definite characteristics of Javier Marias author’s style, as most frequently quoted in our investigation, due to its unconcealed negative evaluation. We mean the saturation of his publications with negatively marked units of all language levels. His usual strategy is to tag or lay up descriptive epithets which we consider the intensificators of publication pragmatic potential. Our attention is as well dedicated to suffix and prefix intensificators and metaphoric means of underlining the expression of emotional component of total expressiveness of Spanish author´s opinion-based journalism.__________References:• Vol'f, M. Funkcional'naja semantika ocenki, 2-e izd., dop. (Moskva: URSS, 2002), 280.• Kuharenko, A. Interpretacija tekstu (Vinnycja: Nova knyga, 2004), 272.• Luk#janova, A. Jekspressivnaja leksika razgovornogo upotreblenija (problemy semantiki) (Novosibirsk: Nauka, 1986), 227• Telija, N. Konnotativnyj aspekt semantiki nominativnyh edinic (Moskva: Nauka, 1986), 142.• Bally, Curso de linguística general (Buenos Aires: Losada, 2007), 315.• Bonstein, Javier Marías, el columnista que lo sabe todo y siempre tiene razón Publicado, https://www.cuartopoder.es/economia/2014/03/14/javier-marias-el-columnista-que-lo-sabe-todo-y-siempre-tiene-razon/7546/• Karpovskaya, «La influencia de los intensificados en la creación de un diferencial de identidad pragmática en la traducción.» Problemas actuales de la filología en el espacio hispano-ruso del conocimiento (Cádiz: Universidad de Cádiz, Servicio de publicaciones, 2013): 73-80.• http://slovopedia.org.ua/37/53395/251382.html• Marías,  «Famosos imbéciles morales II.» El País Semanal (12/9/21): 82.• Marías,  «Pobres turistas y pobre historia.» El País Semanal (16/5/21): 82.• Marías,  «No entiendo.» El País Semanal (19/9/21): 82.• Marías,  «Admiración y agradecimiento.» El País Semanal (23/5/21): 82.• Marías,  «Barcelona desfigurada.» El País Semanal (03/10/21): 82.• Marías,  «Cuento de septiembre.» El País Semanal (26/09/21): 122.• Montero,  «Hablar y abrazar.» El País Semanal (12/9/21): 80.• Montero,  «Aquí, hoy, ahora.» El País Semanal (23/05/21): 80.• Montero, «Odio y miedo.» El País Semanal (26/09/21): 120.• Grandes, «Suyos eran los pájaros.» El País Semanal (26/09/21): 10.• Cercas,  «Ética de los toros.» El País Semanal (24/2/2010): 10.• Torres,  «Nada como mi cúter.» El País Semanal (30/05/2010): 8.
Keywords: intensity, subjectivity, pragmatic potential, opinion-based journalism, intensificator